Tropical Fruit Peel Extracts and Their Potential in Antibacterial Product Formulation: A Literature Review - Hasbi, Nurmi; Rosyunita, Rosyunita; Hanifa, Nisa Isnaeni; Wardoyo, Eustachius Hagni; Rahim, Adelya Riezka (Jurnal Biologi Tropis, 2025)
Bacterial infections caused by pathogenic microorganisms remain a serious global health issue, exacerbated by the increasing incidence of antimicrobial resistance. Although synthetic antibacterial agents are effective, concerns have arisen regarding their long-term toxicity, bioaccumulation, and environmental impact. Consequently, the exploration of natural, safe, and eco-friendly antibacterial sources has gained significant attention. Tropical fruit peels, which are abundant agro-industrial by-products, contain diverse bioactive compounds such as flavonoids, tannins, saponins, and alkaloids that exhibit strong antibacterial potential. This literature review systematically evaluates the potential of tropical fruit peel extracts as active ingredients in antibacterial product formulations. Using a systematic review method, articles were collected from databases such as PubMed and Google Scholar, focusing on studies published between 2015–2025 that assessed the antibacterial activity of ethanol extracts from tropical fruit peels against bacteria including Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Streptococcus mutans, and Klebsiella pneumoniae. The findings indicate that peels of pineapple (Ananas comosus), banana (Musa spp.), mango (Mangifera indica), papaya (Carica papaya), pomelo (Citrus maxima), mangosteen (Garcinia mangostana), and durian (Durio zibethinus) show significant antibacterial activity. These extracts have been successfully formulated into antiseptic soaps, hand sanitizers, nanoemulgels, and herbal mouthwashes, offering effective and sustainable alternatives to synthetic antibacterial agents.